2010
DOI: 10.1111/j.1740-8784.2010.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity: The Influence of Cultural, Social, and Work Contexts

Abstract: The present article aims to answer the question of whether creativity is universal or culture-specific. We develop a conceptual framework that expands the existing knowledge in two ways. First, it distinguishes between the two dimensions of creativity -novelty and usefulness, and their relationship to culture. Second, it clarifies how the social context moderates the relationship between culture and creativity. We focus on the social context where cultural differences are likely to be more salient because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 61 publications
11
203
0
6
Order By: Relevance
“…Some studies have also shown that a high tolerance for uncertainty is associated with greater creativity (Kornilova & Kornilov, 2010;Erez & Nouri, 2010). Finally, high NCC has been related to impulsive decision-making and increased likelihood of anxiety and depression (Rosen et al, 2014).…”
Section: Responses Within the Uncertain Statementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also shown that a high tolerance for uncertainty is associated with greater creativity (Kornilova & Kornilov, 2010;Erez & Nouri, 2010). Finally, high NCC has been related to impulsive decision-making and increased likelihood of anxiety and depression (Rosen et al, 2014).…”
Section: Responses Within the Uncertain Statementioning
confidence: 99%
“…NCC describes the individual's desire to achieve closure in UNCERTAINTY AND IDENTITY 9 order to resolve situational uncertainty or to avoid closure and preserve ambiguity; as with IU and IA, this motivation is located along a continuum (Rosen et al, 2014). While these three constructs overlap, they also capture slightly different aspects of uncertainty-related cognition, affect, and behavior, and all may play an important role in understanding how individual designers interact with uncertainty in the design space.Strong empirical findings link high IU (and high IA to a lesser extent) with affective, cognitive, and behavioral outcomes such as clinically-significant anxiety and depression, increased stress, maladaptive coping, lower quality of life, avoidance of novel situations, information processing and recall biases (favoring absolutists interpretations and recall of uncertainty-marked information), diminished behavioral performance, and impulsive decisionmaking (Birrell, Meares, Wilkinson, & Freeston, 2011;Dugas et al, 2005;Erez & Nouri, 2010;Kornilova & Kornilov, 2010;Luhmann, Ishida, & Hajcak, 2011; Rosen et al, 2014). Some studies have also shown that a high tolerance for uncertainty is associated with greater creativity (Kornilova & Kornilov, 2010;Erez & Nouri, 2010).…”
mentioning
confidence: 99%
“…No contexto da criatividade, não é diferente. Os valores, as crenças, os rituais, dentre outros, podem ser usados no sentido de facilitar, ou de dificultar, um ambiente criativo (Erez & Nour, 2010). Nesse sentido, as práticas, as políticas e as normas podem refletir uma situação de incentivo ou barreira à criatividade coletiva.…”
Section: Cultura Criativaunclassified
“…The notion of creativity as being value-laden and culture specific has been discussed by a number of researchers (e.g. Craft, 2003;Chiu and Kwan, 2010;Erez and Nouri, 2010 Fleith (2011) describes the press for creativity in South America (Brazil) as a socio-cultural and contextually embedded phenomenon, with the effects of cultural factors paralleling those manifested worldwide. In India, the potential of creativity to contribute to economic growth is increasingly recognised, although schools still favour rote learning ).…”
Section: Economic and Cultural Perspectivesmentioning
confidence: 99%
“…Erez and Nouri (2010), working in Israel but reviewing research from around the world, focused on what they describe as the two dimensions of creativity (novelty and usefulness) and the nature of the tasks used (tight or loose) for generating creative thinking and concluded that context was the crucial component for success. Although his work was done in the context of design and technology, is possible to translate Kimbell's (2000) ideas about the processes underpinning creativity into any classroom context.…”
Section: Some Principles Into Practicementioning
confidence: 99%